Easy mesh segmentation - Liu, Jian Xing. (2010)
In recent years, 3D mesh models are widely used in various types of applications. Mesh segmentation now plays an important role towards model understanding, and often acts as a useful tool for various mesh processing applications. This system provides an intuitive and easy to use mesh segmentation tool. Using this system, the user will be able to extract meaningful portions of a mesh. All the user needs to do is to draw one or more simple strokes on the mesh to define their region of interest and also a few more strokes to define the unwanted region. In the random walk approach, the system will divide the mesh into two based on the user input. Basically two portions refer to the region of interest and the unwanted region. After the computations by the system are performed, instant visual feedback is displayed on the user's screen. The user can evaluate the visual output and then save the the respective portions of the mesh into a different files created by the system. This allows the segment of mesh to be re-usable in other applications. Overall, the Easy Mesh Segmentation system requires no professional training for the user. The user friendly interface allows anyone to use the system with ease. Thereby fulfilling its requirement of being an interactive and intuitive tool.